Business Legal Counseling for Micro Entrepreneurs to Prevent Business Disputes in Tembung - Debi Masri; Tina Muhardika Handayani; Bambang Sutejo (Outline Journal of Community Development, 2024)
Business law counseling activities for micro entrepreneurs in Tembung aim to increase legal understanding in running a business and prevent defense. Participated by 50 entrepreneurs from various sectors, this activity included presentations, interactive discussions, and contract drafting practices. Evaluation results show an increase in understanding of business law from 30% to 80%, as well as knowledge of contracts from 25% to 75%. Understanding of settlement solutions also increased from 20% to 70%. Despite the success of the activities, challenges in applying legal knowledge in the field still remain. Therefore, it is recommended to continue the program through workshops and further consultations, in order to support business growth and the local economy in Tembung.